2006
DOI: 10.1097/01.aog.0000220500.83528.6e
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Urinary Tract Injury From Gynecologic Surgery and the Role of Intraoperative Cystoscopy

Abstract: The reasons for higher injury detection rates when routine cystoscopy was performed are unclear. Further study is needed to identify the scenarios where routine cystoscopy is warranted after major gynecologic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(107 citation statements)
references
References 39 publications
4
91
1
4
Order By: Relevance
“…The rate of ureteral injury for vaginal hysterectomy is 0.2 injuries per 1000 cases, and 1.3 injuries per 1000 cases for total abdominal hysterectomy [Gilmour et al 2006]. It has been suggested that this difference in rates between procedures is a result of the selection bias towards transabdominal hysterectomy for cases complicated by infection, previous surgery, and malignancy [Elliott and McAninch, 2006].…”
Section: Gynecologic Surgerymentioning
confidence: 99%
“…The rate of ureteral injury for vaginal hysterectomy is 0.2 injuries per 1000 cases, and 1.3 injuries per 1000 cases for total abdominal hysterectomy [Gilmour et al 2006]. It has been suggested that this difference in rates between procedures is a result of the selection bias towards transabdominal hysterectomy for cases complicated by infection, previous surgery, and malignancy [Elliott and McAninch, 2006].…”
Section: Gynecologic Surgerymentioning
confidence: 99%
“…Urinary tract injuries are reported in approximately 1 percent of women who undergo pelvic surgery 16. In our series, 2.3% of women had urinary tract injuries (7 bladder injuries, 3 ureteric injuries).…”
Section: Resultsmentioning
confidence: 50%
“…Contrast-enhanced CT with delayed imaging, CT cystography, and retrograde urethrography are the diagnostic imaging studies of choice for these JAYPEE injuries. 51 CT cystography with retrograde filling of the bladder followed by helical CT acquisitions is reported to have a 97% sensitivity and 100% specificity for intraperitoneal leakage and 78% sensitivity and 99% specificity for intraperitoneal leakage. Fistulas can also be diagnosed with this method.…”
Section: Postpartum and Postsurgical Complicationsmentioning
confidence: 99%